2020
DOI: 10.1186/s12889-020-08586-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hypertension among persons living with HIV in China: a multicenter cohort study

Abstract: Background: Life expectancy among persons living with HIV (PLWH) has improved with increasing access to antiretroviral therapy (ART), however incidence of chronic comorbidities has simultaneously increased. No data are available regarding the incidence of hypertension among Chinese PLWH. Methods: We analyzed data collected from patients enrolled in two prospective longitudinal multicenter studies of PLWH initiating ART in China. Incidence rate of hypertension per 100 person-years (PYs) among PLWH was calculate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
1
13
2
Order By: Relevance
“…Our findings indicate that the incidence of hypertension was 11.7%, which is lower than what has previously been reported in high-income countries (23)(24)(25) and other studies from Sub-Saharan Africa (26-28). The reason for the difference is not clear but could be related to other factors including diet and ethnicity as well as specific ART regimens.…”
Section: Discussioncontrasting
confidence: 81%
“…Our findings indicate that the incidence of hypertension was 11.7%, which is lower than what has previously been reported in high-income countries (23)(24)(25) and other studies from Sub-Saharan Africa (26-28). The reason for the difference is not clear but could be related to other factors including diet and ethnicity as well as specific ART regimens.…”
Section: Discussioncontrasting
confidence: 81%
“…America 28 and China. 29 The higher incident in this study might be attributed to the lower cut off value (>130/ 80mmhg) to diagnose incident hypertension. Differences in sample size, study design (prospective Vs retrospective cohort), study setting, and socio-demographic characteristics of study participants might be the additional reasons for incidence rate variations.…”
Section: Discussionmentioning
confidence: 64%
“…36,37 However, a similar cohort study in China revealed that zidovudine exposure was a protective factor for hypertension among HIV patients. 29 Controlling high blood pressure is critical in HIV positive individuals to prevent organ damage and ultimately reduce mortality. 38,39 The burden of non-communicable diseases like hypertension in HIV positive patients can be minimized by implementing risk reduction interventions and strategies.…”
Section: Discussionmentioning
confidence: 99%
“…[42] A large number of studies have been published during the past 5 years worldwide on the effect of aging with HIV on non-AIDS associated comorbidities. [43][44][45][46][47] Data from the United States (US) showed that the prevalence of multimorbidities (≥2) among a cohort of more than 22,900 of PLHIV increased from 8% to 22% during a 9-year period of follow-up. [48] Hypertension and hypercholesterolemia were the most common co-occurred comorbidities.…”
Section: Discussionmentioning
confidence: 99%